Book Reviews (The Muslim world, 1926)
Books reviewed in this article Sitte und Recht in Nordafrika. By Ernst Ubach and Ernst Rackow. Stuttgart, Ferdinand Enke. pp. 441. 24 gold marks. Shaman, Saiva and Sufi. A study of the Evolution of Malay Magic. By R. O. Winstedt. Constable & Co., London, pp. 191. 12s. Hespéris. Archives Berbéres et Bulletin de l'Institute des Hautes-Etudes Marocaines. Tome iv, No. 3. Eraile Larose. Paris. La Mecque à la Veille de l'Hégire. By P. H. Lammens, S. J. Mélanges de l'Université Saint-Joseph, Beyrouth. Tome ix, fasc. 3. Abu Amaithal Al-Arabi—Kitab al Ma'thur. Das Buch der Wörter mit gleichem Laut und verschiedener Bedeutung. F. Krenkow. pp. 106. London. A. Probsthain. Das Gesetz der Wüstenbildung in gegenwart and Vorzeit von Johannes Walther. 4th edition revised, pp. 420. Quelle und Meyer, Leipzig. 16 gold marks. Het Boek der Duizend Vragen. Academisch Proefschrift ter verkrijging van den graad van Doctor in de Letteren en Wijsbegeerte, aan de Rijksuniversiteit te Leiden, door Guillaume Frederic Pijper (Boekhandel en Drukkerij voorh. E. J. Brill, Leiden, 1924). pp. 90, plus 131. Malay text. Kleinasiatische Reise. By C. I. Burckhardt. Bremer Presse. München. 1925. pp. 77. Musliheddin Sa'di. Der Rosengarten. München, Hyperionverlag, 1925. pp. 313. Die Religionen. By Edv. Lehmann, D.D. Professor of the History of Religions at the University of Lund. Kurzgeiasste Religionsgeschichte, Leipzig. 1924. Dürr. pp. 128. M. 3. Eine Islamische Apokalypse aus der Kreuzzugszeit. Ein Beitrag zur Djafr-literature. pp. 28. Deutsche Verlagsgesellschait, Berlin. 1924. Rund um die Erde. By E. Büchler. R. Voigtländer, Leipzig, 1925. pp. 267. M. 8. Die Dominikanermissionen des 13. Jahrhunderts. By Dr. Altaner. pp. 248. Frankes Buchhandiung Habelschwerdt (Schlesien) 1925. M. 10. The Gateway of Palestine. A history of Jaffa. By S. Tolkowsky. Geo. Routledge & Sons, Ltd. pp. 190. 10/6. Spiritual and Political Revolution in Islam. By Felix Valyi. Kegan Paul. Treneh, Trubner and Co., London, 1925. 236 “pp. Price 7/6. The Treatise of Al-Jazari on Automata. Leaves from a Manuscript of the Kitab ii Maarifat al-Hiyal a'-Handasiya in the Museum of Fine Arts, Boston, and elsewhere. By Ananda K. Coomaraswamy, D.Sc. (Lond.), Keeper of Indian and Mohammedan Art in the Museum. Folio pp. 19, with 8 plates. Museum of Fine Arts, Boston, 1924. With Lawrence in Arabia. By Lowell Thomas. 408 pp., With illustrations. Price USD4. The Century Company, 1924. Vanished Cities of Arabia. By Mrs. Steuart Erskine, Hutchinson, London. 324 pp. Price 25s net. The Road to Timbuktu. Lady Dorothy Mills. Small, Maynard & Company, Boston. Pp. 262. Wit and Wisdom of India. A collection of humorous folk-tales of the court and countryside current in India. By Pandit Shyama Shankar, M.A. (London). Pp. 102. Price £-/3/6-. George Routledge & Sons, Ltd., London, Broadway House, 68–74 Carter Lane, E. C., 1924. Mysteries of the Libyan Desert: A record of three years of exploration. By W. J. Harding King, F.R.G.S. Seeley, Service and Company, London. pp. 348 with 49 illustrations and 3 maps. 1925. Price 2/ shillings. The Vast Sudan. By Major A. R. Dugmore. 312 pages. Arrowsmith, London, 1924. Amurath to Amurath. By Gertrude Lowthian Bell, 2d Edition. 370 pages. Macmillan. 21s. Dr. Harry Emerson Fosdick's Book “The Modern Use of the Bible.” A Review. By I. M. Haldeman, D.D. Sunday School Times Company, Philadelphia. USD1.00. An Outline of the Religion of Islam. By II. U. Weitbrecht Station, Ph.D., D.D. Pp. 51. Missionary Equipment and Literature Supply, London, 1925. Price one shilling. An Educational Ambassador to the Near East. By Hester Donaldson Jenkins, Ph.D. The Story of Mary Mills Patrick and an American College in the Orient. Fleming H. Revell Company, New York. 1925. pp. 314. Price USD2.50. Illustrated. A Condensed Dictionary, English-Turkish, Pronouncing and Explanatory, Including Current Historical and Geographical Names. By Commander A. Vahid Bey, Turkish Navy. Officially adopted by the Commissariat for Public Instruction of the Turkish Republic. Oxford University Press, American Branch, New York. 1924. pp. 720. Price USD8.50.